¿Estimando el retorno a la educación o a los no observables?: Evidencia de datos de panel - Contreras, Dante; Melo, Emerson; Ojeda, Susana (Estudios de Economía, 2016)
In this paper we investigate the bias due to non observable factors in the estimating of return to schooling for the case of Chile. Using the data from the Casen Survey panel 1996-2001, we estimate a difference model. We find a return to schooling around 9%, which is 2 to 5 percents points lower than found in previous studies.